A STUDY TO ASSESS PRESENTING FEATURES AND EFFECTS OF PREVENTIVE MEASURES DURING THE COVID-19 THIRD WAVE IN RURAL PART OF DISTRICT LUDHIANA, INDIA: A CASE CONTROL STUDY - Lal, Kavisha Kapoor; Lal, Dhruvendra (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: COVID-19 was declared a pandemic by the World Health Organization (WHO) on 11th March 2020. The SARS-CoV-2 virus has mutated over time, which has resulted in genetic variation among population of circulating viral strains over the course of the COVID-19 pandemic. Preventive measures like vaccination, social distancing, using of face mask and hand hygiene practices played a vital role in mitigating the spread of this pandemic. But were these measures effective enough to curtail this pandemic. Purpose: To assess the presenting features of COVID 19 in the third wave and to assess the effectiveness of preventive measures against COVID 19 during the third wave. Methods: This is a hospital based prospective study where participants were regularly followed up till 14 days, conducted in rural part of North of India. Results: A total of 239 participants were included in this study. The study found that 95% of these participants received first dose of COVID vaccine as compared to 49.8% who received second dose. Some of the participants (39.7%) were not obeying the norms of social distancing. 52.1% of the subjects were using masks, which has been proven to be one of the effective measures for prevention of transmission of COVID 19. 71.1% were practicing hand hygiene measures. Conclusion: Vaccination and using face mask were significantly associated with mitigating the spread of COVID-19 among rural population who visited the health care facility.